(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This study investigates the clinical and experimental dynamics of renal parenchymal and microcirculatory damage in arterial hypertension developing on the background of diabetes mellitus. A combined clinical and experimental approach was applied, including patients with diabetes-associated arterial hypertension and an experimental model reproducing diabetic-hypertensive renal injury. Renal functional parameters, microcirculatory alterations, and morphological changes of the renal parenchyma were analyzed at different stages of disease progression using laboratory, instrumental, and histological methods. The results demonstrate that the coexistence of diabetes mellitus and arterial hypertension leads to an accelerated progression of renal damage, beginning with early microcirculatory dysfunction and subsequently resulting in structural alterations of glomerular and tubular components. Progressive impairment of microcirculation plays a key role in renal tissue hypoxia, inflammatory responses, and fibrotic remodeling. Early detection of microvascular disturbances may therefore be crucial for preventing irreversible renal parenchymal damage in patients with diabetes-associated arterial hypertension.